Fetal birth weight, a challenge to the mother and simplest marker for fetal maturity: a study in new rural hospital setup - Nagarashi, Rajashree Dattatreya; Durvasula, Lakshmi Swapna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The birth weight is an important factor which the obstetricians have to give due importance when contemplating elective induction of labor before 40 completed weeks. It is a single most important determinant for survival, growth and development of infant. It reflects the health status of the mother during adolescence and pregnancy and also the quality of antenatal care. It is well known that there is a co-relation between weight of the fetus and the length of the gestation and other various factors. This study looks into the various factors influencing the fetal birth weight and length of gestation and what is its relative importance to the viability of developmental chances of premature infants and also infants born at term. Objective was to study the effect of various maternal factors like maternal age, parity, maternal weight, gestational age on fetal birth weight. Methods: 176 participants with term pregnancies were studied under three independent variables viz gestational age, maternal age and maternal weight that had effect on the fetal birth weight in two groups - primipara and multipara and reported by statistical analysis. Results: The independent variables gestational age and maternal weight showed a statistically significant correlation (p <0.05) with fetal birth weight in both the groups. Whereas the variable maternal age didn’t have any statistically significant effect (p >0.05) on the fetal birth weight in the study. Conclusions: Primipara had more pronounced correlation with fetal birth weight than multipara in the variable gestational age. The maternal weight affected fetal birth weight equally in both the groups. And maternal age had no effect on fetal birth weight in either groups.